Human Supplementation with AM3, Spermidine, and Hesperidin Enhances Immune Function, Decreases Biological Age, and Improves Oxidative–Inflammatory State: A Randomized Controlled Trial - Judith Félix; Estefanía Díaz-Del Cerro; Adriana Baca; Ana López-Ballesteros; María José Gómez-Sánchez; Mónica De la Fuente (Antioxidants)
The positive effect of AM3, spermidine, and hesperidin, which have antioxidant and anti-inflammatory properties, on immunity is known, but their effect on the rate of aging, known as biological age (BA), is unclear. This work aims to test if the intake of a blend of AM3 (150 mg), spermidine (0.6 mg), and hesperidin (50 mg) for 2 months could decrease BA and improve immunity, redox, and inflammatory states. For this, 41 participants (30–63 years) were randomly divided into placebo and supplement groups. The supplement group took two capsules daily with AM3, spermidine, and hesperidin for two months, while the placebo group took capsules containing only calcium phosphate and talcum powder. Before and after the treatment, peripheral blood was collected. Immune function was assessed in leukocytes, redox state in whole-blood cells, erythrocytes, and plasma, and cytokine concentration in both mononuclear cell cultures and plasma. Finally, the Immunity Clock model was applied to determine BA. The results show that the intake of this blend improves the immune functions that constitute the Immunity Clock, decreasing BA by 11 years and reducing the oxidative–inflammatory state of the participants. Therefore, this supplement can be proposed as a strategy to rejuvenate BA and achieve healthy aging.